Surgery for Inflammatory Tumor of the Lung Caused by Pulmonary Actinomycosis - Schweigert, M.; Meyer, C.; Stadlhuber, R. J.; Dubecz, A.; Kraus, D.; Stein, H. J. (The Thoracic and Cardiovascular Surgeon, 2012)
Background Actinomycosis is an uncommon chronic suppurative bacterial infection caused by anaerobic bacteria. Pulmonary actinomycosis is even more infrequent and generally simulates a wide variety of pulmonary disorders including tuberculosis and lung cancer. Therefore delayed diagnosis and misdiagnosis is common. Here, actinomycosis was initially confused with pulmonary carcinoma.Methods We report on three cases of inflammatory tumors caused by pulmonary actinomycosis. All three patients were male and had a history of alcoholism and poor oral hygiene associated with dental disease. Clinical symptoms were nonspecific and radiographic imaging showed tumor-like mass lesions not distinguishable from neoplasms. Preoperative bronchoscopy, sputum culture, laboratory tests and bronchoalveolar lavage neither confirmed an infectious disease nor ruled out lung cancer. Hence all patients underwent thoracotomy for both diagnosis and definitive treatment. Intraoperatively we encountered a necrotizing infection forming cavitary as well as tumorous lesions and a lobectomy was performed due to destroyed lung tissue. In one case the tumorous lesion involved the chest wall so that partial resection of the 3rd rib with the adjacent soft tissue was mandatory.Results Histological examination of the pulmonary specimen established the diagnosis of pulmonary actinomycosis. All patients recovered well and received antibiotic therapy with oral penicillin.Conclusions The diagnosis of pulmonary actinomycosis remains challenging. In cases of an inflammatory tumor imitating lung cancer, surgical resection is mandatory, both to confirm the diagnosis and for the definitive treatment in cases with irreversible parenchymal destruction. Here, surgery in combination with medical treatment offered reliably excellent results.
Keywords: pulmonary actinomycosis; cavitary pulmonary disease; lung infection; septic thoracic surgery; pleural empyema